2019
DOI: 10.1002/jper.19-0130
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial function of the polyunsaturated fatty acid KetoC in an experimental model of periodontitis

Abstract: Background The bioactive metabolite KetoC, generated by intestinal bacteria, exerts various beneficial effects. Nevertheless, its function in the pathogenesis of periodontitis remains unclear. Here, we investigated the effect of KetoC in a mouse model of periodontitis and explored the underlying mechanism. Methods Thirty‐one 8‐week‐old male C57BL/6N mice were randomly divided into four groups (non‐ligation, non‐ligation + KetoC, ligation + Porphyromonas gingivalis, and ligation + P. gingivalis + KetoC) (n = 7/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 46 publications
2
27
0
Order By: Relevance
“…They summarized that oral gavage or a combination of oral gavage and ligature-induction might be a good strategy for studying inflammatory markers and epigenetic changes in experimental periodontal disease and better for modeling human periodontal disease compared to the simple ligature model. In addition to the aforementioned methods, there is another method to promote periodontitis by orally administering P. gingivalis to a ligature-induced periodontitis model; however, few studies have used this method, and it may not be considered to be a common way to induce periodontitis [175,192].…”
Section: Periodontitis Model Induced By Ligation and Oral Gavage Of P Gingivalismentioning
confidence: 99%
“…They summarized that oral gavage or a combination of oral gavage and ligature-induction might be a good strategy for studying inflammatory markers and epigenetic changes in experimental periodontal disease and better for modeling human periodontal disease compared to the simple ligature model. In addition to the aforementioned methods, there is another method to promote periodontitis by orally administering P. gingivalis to a ligature-induced periodontitis model; however, few studies have used this method, and it may not be considered to be a common way to induce periodontitis [175,192].…”
Section: Periodontitis Model Induced By Ligation and Oral Gavage Of P Gingivalismentioning
confidence: 99%
“…Anti-inflammatory activity has become a treatment strategy for periodontitis ( Sulijaya et al, 2019 ). Fermented milk with Lactobacillus helveticus LH-2 and its fraction peptide F5 increased TNF-α, IL-1β, and IL-6 through stimulation of macrophages with production of nitric oxide and phagocytic activity, which showed that the F5 peptide fraction could modulate macrophage functions ( Tellez et al, 2010 ).…”
Section: Probiotics-mediated Bioconversion (Pmb) and Periodontitismentioning
confidence: 99%
“…Glycosylated caseinomacropeptide, produced by hydrolyzing the κ-casein phenylalanine-105 and methionine-106 peptide bonds by the action of chymosin in the process of milk fermentation, inhibited the entry of toxins, pathogenic adhesion to the cell wall, and infections by oral pathogens such as P. gingivalis, S. mutans, and Streptococcus sobrinus ( Córdova-Dávalos et al, 2019 ; Malkoski et al, 2001 ). KetoC inhibited the growth of P. gingivalis in vitro and reduced alveolar bone destruction in a periodontitis mouse model ( Sulijaya et al, 2019 ). Furthermore, fluorescence microscopy after LIVE/DEAD bacterial staining of KetoC-treated P. gingivalis cells showed that KetoC decreased the viability of the bacteria ( Sulijaya et al, 2019 ).…”
Section: Probiotics-mediated Bioconversion (Pmb) and Periodontitismentioning
confidence: 99%
See 2 more Smart Citations